Corporate social responsibility and health promotion campaigns among major U.S. professional sporting leagues - Rugg, A. (Health Communication and Sport. Connections, Applications, and Opportunities, 2022)
Health Communication and Sport: Connections, Applications, and Opportunities aggregates sport and health communication into a collective resource that advances scholarly inquiry at the intersection of these two fields. Through bringing together a collaborative of scholars and practitioners who are doing work in areas ranging from mental health, to media, to youth sports, and social media, this volume evaluates health communication issues in sport contexts and inspires work that will answer contemporary questions and problems.